Contributing Forces in Entrepreneurship Research: A Global Citation Analysis. (26th September 2017) - Xu, Nianhang; Chen, Yining; Fung, Anna; Chan, Kam C.
Abstract : We use Resource Dependency Theory and Human Capital Theory to explain entrepreneurship research, which is a relatively new research field over the last decade. Using citation analysis based on a rich database of 191, 695 citations on 2, 154 entrepreneurship articles published in leading journals from 2002 to 2013, we find that geographic diversity, international collaboration, top research scholars, and top research institutions enhance entrepreneurship research quality, which is measured by the number of citations per article. Leading institutions in entrepreneurship research are not long‐established research institutions. Entrepreneurship presents itself as a unique opportunity for a wider range of institutions and scholars to collaborate and develop expertise and leadership research.